2022
DOI: 10.1007/s00221-022-06449-w
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of social isolation on mesolimbic dopamine release

Abstract: In humans, social isolation is a known risk factor for disorders such as substance use disorder and depression. In rodents, social isolation is a commonly used environmental manipulation that increases the occurrence of behaviors related to these disorders. Age is thought to influence the effects of social isolation, but this predictive relationship is not well-understood. The present study aimed to determine the effects of social isolation on mesolimbic dopamine release at different developmental age points i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Consequently, the experience of social isolation is aversive and impacts both our brains and our behaviors. While long-term isolation can lead to the emergence of anti-social behaviors in both humans and rodents Arrigo and Bullock, 2008;Check et al, 1985;Hossain et al, 2020;Killgore et al, 2021;Ma et al, 2011Ma et al, , 2022Machimbarrena et al, 2019;Matsumoto et al, 2005;Mears and Bales, 2009;Reid et al, 2022;Toth et al, 2011;Valzelli, 1973;Weiss et al, 2004;Wiberg and Grice, 1963;Zelikowsky et al, 2018), short-term isolation typically increases levels of social motivation and promotes social-seeking behaviors (Baumeister and Leary, 1995;Cacioppo et al, 2006;Cacioppo and Cacioppo, 2018;House et al, 1988;Lee et al, 2021;Niesink and van Ree, 1982;Panksepp and Beatty, 1980;Zhao et al, 2021). Alterations in social motivation are characteristic of many neurodevelopmental disorders, including autism spectrum disorder (Chevallier et al, 2012;Clements et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the experience of social isolation is aversive and impacts both our brains and our behaviors. While long-term isolation can lead to the emergence of anti-social behaviors in both humans and rodents Arrigo and Bullock, 2008;Check et al, 1985;Hossain et al, 2020;Killgore et al, 2021;Ma et al, 2011Ma et al, , 2022Machimbarrena et al, 2019;Matsumoto et al, 2005;Mears and Bales, 2009;Reid et al, 2022;Toth et al, 2011;Valzelli, 1973;Weiss et al, 2004;Wiberg and Grice, 1963;Zelikowsky et al, 2018), short-term isolation typically increases levels of social motivation and promotes social-seeking behaviors (Baumeister and Leary, 1995;Cacioppo et al, 2006;Cacioppo and Cacioppo, 2018;House et al, 1988;Lee et al, 2021;Niesink and van Ree, 1982;Panksepp and Beatty, 1980;Zhao et al, 2021). Alterations in social motivation are characteristic of many neurodevelopmental disorders, including autism spectrum disorder (Chevallier et al, 2012;Clements et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation in male rats does not affect basal NAc DA in microdialysis studies (Novoa et al, 2021), which is consistent with our findings. Social isolation increased ES-induced DA release in NAc, using FSCV, in adult male mice but did not find an effect of housing in adolescent males (McWain et al, 2022). Another study examined social isolation compared to group housing in males and found that socially isolated males had higher DA release (Yorgason et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Meaningful age comparisons across mammalian clades are difficult; however, this age has been considered late middle adulthood (or roughly 50 human years). 43,44 Sections were rinsed in PBS, blocked in 5% normal donkey serum (NDS) for 30 minutes at room temperature, and incubated on a shaker in rabbit anti-GFP IgG (1:500; Abcam #ab6556), rat anti-mTFP IgG (1:200; Ximbio #155264), and guinea pig anti-TagRFP IgG (1:500; Ximbio #155267), with 3% NDS and 0.5% TX in PBS for 3 days at 4°C. The anti-GFP and anti-TagRFP antibodies recognize EYFP and TagBFP, respectively.…”
Section: Animalsmentioning
confidence: 99%